Analisis Penerapan Kurikulum Merdeka dalam Meningkatkan Kemampuan Representasi Matematis Siswa - Ega Ismaya; Ita Yusritawati (Indo-MathEdu Intellectuals Journal, 2023)
The development of the education curriculum in Indonesia, particularly the 2021 Merdeka Curriculum, focuses on instilling character education through P5 (Penguatan Profil Pelajar Pancasila Project). However, students still face difficulties in understanding mathematics, particularly mathematical representation. This study employs a qualitative descriptive method to evaluate the implementation of the Merdeka Curriculum in enhancing mathematical representation skills in Grade VII-B at SMP Negeri 2 Cibeureum. Data is collected through observations, tests on mathematical representation abilities, and student interviews. The findings indicate that most students possess moderate mathematical representation skills, with the Merdeka Curriculum playing a vital role in enhancing these skills through active interactions. Students with lower proficiency require a deeper approach and social support. Interviews reveal positive changes in the learning process, yet as per the observational results, some students remain inactive in the learning process. The full objectives of the Merdeka Curriculum have not been entirely achieved. The teacher interview results reveal implementation barriers, such as selecting teaching models that match students' learning styles. Teachers strive to overcome these barriers through reflection, discussions with colleagues, and the creation of more engaging teaching models.